Liver Transplantation for Hepatic Adenoma: A UNOS Database Analysis and Systematic Review of the Literature. Issue 2 (5th January 2022) - Ziogas, Ioannis A.; Tasoudis, Panagiotis T.; Serifis, Nikolaos; Alexopoulos, Sophoclis P.; Montenovo, Martin I.; Shingina, Alexandra
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Liver transplantation (LT) has been employed for hepatic adenoma (HA) on a case-oriented basis. We aimed to describe the characteristics, waitlist, and post-LT outcomes of patients requiring LT for HA. Methods: All patients listed or transplanted for HA in the United States were identified in the United Network for Organ Sharing (UNOS) database (1987–2020). A systematic literature review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-analysis statement. Results: A total of 199 HA patients were listed for LT in UNOS and the crude waitlist mortality was 9.0%. A total of 142 HA patients underwent LT; 118 of these were among those listed with an indication of HA who underwent LT, and 24 were diagnosed incidentally. Most did not experience hepatocellular carcinoma transformation (89.4%). Over a median follow-up of 62.9 mo, death was reported in 18.3%. The 1-, 3-, and 5-y patient survival rates were 94.2%, 89.7%, and 86.3% in the UNOS cohort. The systematic review yielded 61 articles reporting on 99 nonoverlapping patients undergoing LT for HA and 2 articles reporting on multicenter studies. The most common LT indications were suspected malignancy (39.7%), unresectable HA (31.7%), and increasing size (27.0%), whereas 53.1% had glycogen storage disease. Over a median follow-up of 36.5 mo, death was reported in 6.0% (n=5/84). The 1-, 3-, and 5-y patient survival rates were all 95.0% in the systematic review. Conclusions: LT for HA can lead to excellent long-term outcomes in well-selected patients. Prospective granular data are needed to develop more optimal selection criteria and further improve outcomes.